Family Nursing Care for Clients With Diabetes Mellitus in Community Health Center - hastutik, annasikah sustyo; fata, ulfa husnul; romadhon, wimar anugrah (Health Gate, 2025)
Diabetes Mellitus (DM) is a growing public health problem in Indonesia, particularly among the elderly. Type 2 DM develops slowly and is closely linked to unhealthy lifestyles. Elderly people with DM require family support to prevent complications and improve their quality of life. This study aims to describe the implementation of family nursing care for DM patients at the Sananwetan Community Health Center in Blitar City. The research design was a case study involving four families with elderly people with DM. The nursing care process consisted of assessment, diagnosis, planning, implementation, and evaluation. The instruments used included the family assessment format, the Indonesian Nursing Diagnosis Standards (SDKI), the Indonesian Nursing Outcome Standards (SLKI), and the Indonesian Nursing Intervention Standards (SIKI). Implementation was carried out through an educational approach using leaflets and calendars containing information about acupressure therapy and DM management. This study identified six nursing diagnoses: ineffective family health management, readiness to improve family coping, unstable blood glucose levels, knowledge deficit, readiness to improve knowledge, and non-compliance. The interventions provided demonstrated improved family knowledge, active involvement in care, and patient adherence to diabetes treatment and management. Family nursing care with an educational approach and supporting media has proven effective in enhancing the family's role in diabetes management in the elderly. Family support is a key factor in successful disease control. It is recommended that families continue to develop health management skills, healthcare providers improve family education, and community health centers strengthen ongoing education programs.